Upaya Meningkatkan Motivasi Belajar Siswa Pelajaran Pendidikan Agama Islam - Ahmad Mirza Ardyanto; Nur Jannah (Yayasan Darusssalam Bengkulu, 2024)
The technique or method used to collect research data is in accordance with the research instrument. If the data collection method chosen is the interview method, then the evaluation tool is the interview guideline. If the data collection method is the observation method, then the evaluation tool is the observation sheet. If the data collection method is a questionnaire, then the evaluation tool is the questionnaire document method, the evaluation tool is the guideline, if the data collection method is the test method, the evaluation tool is the test method, the price is the test (Suharsimi Arikunto, 2014). From the comments above, in this study the following specific data collection methods were used: Measurement techniques are quantitative ways of collecting research data or producing numbers. The measuring instrument used is a written test with different formats and scales. (Dwi Agus Sudjimat, 2014: 69). Testing as a data collection tool is a series of questions or exercises used to measure the knowledge, intelligence, abilities, or talents of individuals or groups. To find out student learning achievement, at the end of the cycle, each student is given an academic achievement test or academic achievement test.